Friction mechanisms and abrasion of the human finger pad in contact with rough surfaces - Derler, S.; Preiswerk, M.; Rotaru, G.-M.; Kaiser, J.-P.; Rossi, R.M. (Tribology international, 2015)
The friction and abrasion behaviour of the finger pad on abrasive papers was investigated in friction experiments, combined with microscopic analyses and a protein assay to quantify skin particles abraded in friction contacts. Friction measurements at varied normal forces resulted in relatively high and load-independent friction coefficients, pointing to ploughing and abrasion as important friction mechanisms. The microscopic analyses revealed that large numbers of skin particles are abraded in form of single corneocytes, corneocyte fragments and agglomerates of corneocytes. In addition, micro-scratches were observed on the epidermal ridges of the finger pad after friction contacts. In friction measurements at the same conditions, the amount of abraded skin particles varied for abrasive papers with different roughness, while friction coefficients were comparable. •The friction and abrasion of the finger pad on glass and abrasive papers was analysed.•Ploughing and abrasion are important friction mechanisms of skin on abrasive papers.•Friction measurements of skin are combined with microscopic and protein analysis.•A protein assay showed that the amount of abraded skin varies with roughness.